Design for improved solar shading control - Littlefair, P. J. (TM (Chartered Institution of Building Services Engineers) ;, 2006)
This publication provides guidance on the design of facades to incorporate appropriate levels of solar shading, and gives information on some of the design options available. Avoiding overheating due to solar gain is a key design requirement to minimise the use of mechanical cooling and reduce energy consumption by cooling systems. Good low energy design will seek to minimise the effect of excessive solar gains in summer by appropriate orientation, massing and selection of the building facade. However, additional measures may still be required to provide solar shading to the building to reduce solar gains and the associated risk of overheating. The guidance in this CIBSE TM demonstrates how designers can address the issue of solar gain, ensuring that the building is able to benefit from solar gains when appropriate without suffering problems of excessive gains in summer. Under Part L of the 2006 Building Regulations for England and Wales, there is now an explicit requirement to limit heat gains to buildings. This will involve assessing designs of naturally ventilated buildings to ensure that they will not suffer from overheating in summer. --